1995
DOI: 10.1038/bjc.1995.451
|View full text |Cite
|
Sign up to set email alerts
|

Endocrinological and clinical evaluation of exemestane, a new steroidal aromatase inhibitor

Abstract: Summary The androstenedione derivative, exemestane (FCE 24304), is a new orally active irreversible aromatase inhibitor. Fifty-six post-menopausal advanced breast cancer patients entered this study to evaluate the activity of four low exemestane doses in reducing oestrogen levels. The drug's tolerability and clinical efficacy were also assessed. Exemestane was orally administered to four consecutive groups at daily doses of 25, 12.5, 5 and 2.5 mg, and the changes in oestrogen, gonadotrophins, sex-hormone bind… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
35
0
2

Year Published

1998
1998
2023
2023

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 74 publications
(40 citation statements)
references
References 19 publications
(9 reference statements)
3
35
0
2
Order By: Relevance
“…The rise in the aromatase substrates, testosterone and androstenedione, is probably secondary to substrate accumulation and/or to the feedback increase in gonadotropins caused by aromatase blockade. The 21% decrease in SHBG concentrations caused by 25 mg exemestane confirms the observation in postmenopausal women (20).…”
Section: Discussionsupporting
confidence: 73%
“…The rise in the aromatase substrates, testosterone and androstenedione, is probably secondary to substrate accumulation and/or to the feedback increase in gonadotropins caused by aromatase blockade. The 21% decrease in SHBG concentrations caused by 25 mg exemestane confirms the observation in postmenopausal women (20).…”
Section: Discussionsupporting
confidence: 73%
“…Phase I/II studies in patients with advanced breast cancer, it has demonstrated significant antitumor activity and favorable toxicity profile. [52][53][54][55] More importantly, in a phase III study, as second line treatment in patients with advanced breast cancer, exemestane was equivalent to Megace in objective response, but was significantly superior to Megace in duration of overall success, time to progression, time to treatment failure and OS. 38 Eligible patients for the B-33 trial must have completed approximately 5 years of adjuvant tamoxifen therapy, must be postmenopausal, and disease free at the time of randomization.…”
Section: Studies In Patients With Er-positive Tumorsmentioning
confidence: 99%
“…The time to obtain maximal estradiol (E2) suppression is 2-4 days for anastrozole and 7 days for exemestane, 14,15 but both anastrozole and exemestane achieve a steady state drug level by day seven. 16 A comparable inhibition in excess of 90%, of in vivo aromatase activity has been observed with both classes of aromatase inhibitors. While both anastrozole and exemestane are hepatically metabolized unlike anastrozole, exemestane is a major substrate of the CYP3A4 enzyme system in the liver.…”
Section: Mechanism Of Action Metabolism and Pharmacokinetic Profilementioning
confidence: 78%